Effectiveness of group cognitive behavioural therapy on depression, negative automatic thoughts, anxiety, self-esteem and anger among adolescents in sheltered homes - Ding, Wai Eng (2021)
Literature on adolescents residing at sheltered homes and the effectiveness on group cognitive behavioural therapy (gCBT) for treating adolescent emotional distress are scarce in Malaysia. In Phase 1, this study aimed to determine the prevalence and associated factors of depression, anxiety, negative automatic thoughts, self-esteem, and anger among adolescents residing at Malay-operated non-government-run sheltered homes in Selangor, Malaysia. In Phase 2, a randomised controlled trial (RCT) aimed to examine the effectiveness of gCBT (SAHABAT programme) compared to waitlist control on depression, anxiety, negative automatic thoughts, selfesteem, and anger in orphaned adolescents residing at sheltered homes di Selangor. Phase 1. Six hundred thirty-two adolescents aged 13 to 17 years from 17 out of 417 Malay-operated non-government-run sheltered homes completed a set of questionnaires (n = 281 from non-tahfiz-based sheltered homes; n = 351 from tahfizbased sheltered homes). Data analysis involved descriptive statistics, t-tests, and generalised linear mixed model (GLMM). The number of non-orphans (n = 335; 53%) and orphans (n = 297; 47%) were almost equal. The prevalence from mild to severe symptomatology of depression and anxiety in this study were 70.9% and 82.3% respectively, with 64.1% for comorbidity of both symptomatology. Next, the prevalence of having negative automatic thoughts from sometimes to very often was 100.0%. Meanwhile, the prevalence of low and high self-esteem were 22.6% and 77.4% respectively. The prevalence of anger symptomatology from mild to extremely elevated anger was 37.4%. Age, anxiety, negative automatic thoughts, self-esteem and anger were significantly associated with depression. Depression, negative automatic thoughts, and anger were significantly associated with anxiety. In addition, depression, anxiety, self-esteem, and anger were significantly associated with negative automatic. thoughts. Meanwhile, self-esteem was not significantly related to anxiety and anger. When depression, anxiety, and anger increased, more frequent negative automatic thoughts were reported. Adolescents who had low self-esteem had higher scores for depression, anxiety, negative automatic thoughts and anger than those who had high self-esteem. The prevalence of depression, anxiety, and negative automatic thoughts are high among adolescents residing at sheltered homes. Modifying negative thoughts in therapy is crucial as it is associated with most psychological variables. Phase 2. Nine out of 17 sheltered homes were allocated to either the intervention group (4 homes, n = 71) or waitlist control group (5 homes, n = 68). The participants of the RCT consisted of orphaned adolescents only. The intervention group attended 8 biweekly sessions of SAHABAT programme over one month. Data were measured across 6 time-points, namely, pre-, mid-, and immediate post-intervention, and 1- month, 3-month, and 6-month post-intervention. Data analysis involved descriptive statistics, t-tests, and generalised linear mixed model (GLMM). SAHABAT programme was superior to waitlist control in reducing symptomatology of depression, anxiety, negative automatic thoughts, and anger, and increasing selfesteem across time from pre-intervention to 6-month post-intervention. These findings have bridged the research gap in providing evidence-based for gCBT in treating adolescent emotional distress in Malaysia. These findings signal the outreach for identifiying emotional distress in adolescents residing at sheltered homes and psychological services for this population.